Coronavirus Disease-19 Pandemic and Dermatology. What to Expect? - Brishkoska-Boshkovski, Vesna; Vasileva, Mirela; Dimitrovska, Irena; Grivcheva-Panovska, Vesna (Open Access Macedonian Journal of Medical Sciences, 2020)
The novel coronavirus (CoV), CoV disease (COVID)-19, and the ongoing pandemic, is changing every aspect of the human life. Furthermore, the COVID-19 pandemic has a profound impact on health-care worldwide, with no exception in dermatology care units. At the time of pandemic, constant fear and stress are present on the surface. Skin diseases are the most common somatic causes of psychological disorders and, conversely. During a stressful situation, the body has power to adjust and to maintain its well-being, but with prolonged exposure to stress, the first negative changes such as fear, anxiety, and depression will eventually lead to chronic fatigue and an increased risk of disease. The proportion of patients reporting emotional triggers varies with the disease, ranging from approximately 50% in acne to 90% in rosacea, alopecia areata, psoriasis, neurotic excoriations, and lichen simplex and may be 100% for patients with hyperhidrosis. In this paper, we will look at the most common psychodermatological disorders and its implication in the era of COVID-19 pandemic. According to all the pathophysiological conditions that indicate the association of skin diseases with stress, it is normal to expect their deterioration and occurrence in this pandemic period. We will be witnessing a growing number in patients’ consultations with chronic urticaria, dermographism, worsening rosacea, generalization, and relapses of psoriasis. It is needed to be prepared for as many cases as possible, because the psychological consequences will still be felt. We encourage more comprehensive studies of the implications of the COVID-19 pandemic in these patients.